Peritoneal carcinomatosis in non-small-cell lung cancer: retrospective multicentric analysis and literature review. (25th January 2019) - Abbate, Maria Ida; Cortinovis, Diego Luigi; Tiseo, Marcello; Vavalà, Tiziana; Cerea, Giulio; Toschi, Luca; Canova, Stefania; Colonese, Francesca; Bidoli, Paolo
Aim: We investigated outcomes in patients with advanced non-small-cell lung cancer (NSCLC) and peritoneal involvement.Patients & methods: NSCLC patients with peritoneal carcinomatosis (PC) were included. We evaluated mOS1 (overall survival [OS] from NSCLC diagnosis) and mOS2 (OS from diagnosis of PC).Results: In total, 60 NSCLC patients were diagnosed with PC, 12 (20%) patients had a diagnosis of NSCLC and synchronous PC with a median OS of 9 months. Smokers had a shorter mOS1 and mOS2 compared with never-smokers; EGFR -mutated patients on tyrosine kinase inhibitors had longer mOS1 and mOS2 than EGFR wild-type patients.Conclusion: Metachronous PC is correlated to a short survival, irrespective of treatment line. Never-smokers and EGFR -mutated patients had improved mOS1 and mOS2 when compared with smokers and EGFR wild-type population.